(untitled) (Proceedings of the International Conference on Future of Education, 2018)
The study aimed to compare students’ English learning achievement between employing the Technological Pedagogical Content Knowledge Process (TPCK Process) and a conventional teaching method as well as to compare the English learning achievement of students before and after using the TPCK Process among 80 undergraduate students selected by the random sampling method. The students were divided into two groups; 40 students in the controlled group treated by a conventional teaching method and the other 40 students in the experimental group treated by the TPCK Process. The research instruments were twelve TPCK Process lesson plans, twelve conventional method lesson plans, and fifty items of English achievement test with difficulty index between 0.23-0.78, index of discrimination between 0.28- 0.83, and its internal reliability at 0.86. Mean, percentage, standard deviation and t-test were used to analyze the collected data. The results revealed that the English learning achievement of students treated by TPCK Process was higher than those treated by the conventional teaching method at the significant level of p < .05, and students’ English learning achievement was higher than after using TPCK process at the significant level of p < .05.